State of the World's cities 2004/2005 : globalization and urban culture - United nations Human settlements programme (London, 2004)
'This report not only documents problems in the world's cities, it directs our attention to policies, programmes and projects that can help to create multicultural and inclusive cities. As the report emphasizes ... we need to plan for cities of difference, and capitalize on the benefits of multicultural existence. This requires the engagement of all non-governmental and community stakeholders, on the basis of legislation that guarantees citizens' rights to the city, and judicial systems that enforce those rights. By addressing the relationship between globalization, culture and poverty within cities, this report will help the assessment of progress towards the attainment of the Millennium Development Goals and Targets, particularly those relating to slums, water and sanitation. Its conclusions stand as a clear challenge to city planners and managers to nurture an urban culture of peace - one that supports the eradication of poverty and ensures that all urban dwellers, regardless of their race, sex, language or religion, are full citizens of the cities in which they live' From the foreword by Kofi Annan, Secretary-General, United Nations As towns and cities grow at unprecedented rates, sustainable urbanization is on of the most pressing challenges facing the global community in the 21st century. Cities are the hub og much national production and consumption - economic and social processes that generate wealth and form urban culture. The State of the World's Cities 2004/2005 looks at how this potential can be used to address current challenges and create dynamic, multicultural and inclusive urban settings. Using extensive examples and illustrations, and with contributions from many of the world's leading urban scholars, it lays out the conditions for a new culture of planning, involving civil society as well as public authorities, to ensure participation of even the most marginalized sectors
Keywords: Economic development